1999
DOI: 10.1042/bj3380139
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the 70 kDa polypeptide of the Na/Ca exchanger

Abstract: The Na/Ca exchanger is associated with 160, 120 and 70 kDa polypeptides whose nature is poorly understood. We have purified and characterized the Na/Ca exchanger from bovine cardiac sarcolemmal vesicles (SLVs) by using ion-exchange and affinity chromatographies. The Na/Ca exchanger-enriched fraction was reconstituted into asolectin liposomes [lipid to protein ratio 10:1 (w/w)] that showed Na/Ca exchange activity. Under non-reducing conditions, SDS/PAGE showed a single 70 kDa polypeptide, which was further char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Although the presence of a Na ϩ ͞Ca 2ϩ exchange mechanism in bovine sperm plasma membrane vesicles has been suggested (30), the present study demonstrates the presence of such an exchanger on the surface of intact sperm. Not only does the Na ϩ ͞Ca 2ϩ exchanger in herring sperm comigrate with the canine myocyte polypeptide at 120 kDa, a 70-kDa band was recognized by the antibody in some preparations, which corresponds to a proteolytic degradation product or subunit of the exchanger (31,32). Interestingly, the Na ϩ ͞Ca 2ϩ exchanger localization studies produced similar binding patterns as a study (17) that localized SMIF-binding sites over the entire sperm surface, with the majority of label over the midpiece region.…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of a Na ϩ ͞Ca 2ϩ exchange mechanism in bovine sperm plasma membrane vesicles has been suggested (30), the present study demonstrates the presence of such an exchanger on the surface of intact sperm. Not only does the Na ϩ ͞Ca 2ϩ exchanger in herring sperm comigrate with the canine myocyte polypeptide at 120 kDa, a 70-kDa band was recognized by the antibody in some preparations, which corresponds to a proteolytic degradation product or subunit of the exchanger (31,32). Interestingly, the Na ϩ ͞Ca 2ϩ exchanger localization studies produced similar binding patterns as a study (17) that localized SMIF-binding sites over the entire sperm surface, with the majority of label over the midpiece region.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, in one portion of the protein, chymotrypsin cleaves the exchanger at multiple sites, and the fragments are too small to be detected in the gel system. In two studies, the N terminus of the 70-kDa proteolytic fragment has been identified to coincide with the N terminus of the full-length protein (27) or to begin within the intracellular loop in the 257-269-residue region (28).…”
Section: Split Na ϩ -Ca 2ϩ Exchangersmentioning
confidence: 99%
“…We used the recombinant plasmid to express V5/His-tagged NCX1.5 in HEK293 cells. Immunoblot analysis using anti-V5 antibody revealed that transfection of HEK293 cells with the NCX1.5-V5/His plasmid resulted in a single broad band in lysates with a molecular mass of 120 kDa, a component of the native full-length exchanger (9). These findings suggest that the NCX1.5-V5/His plasmid-transfected HEK293 cells highly expressed the full-length NCX1.5 tagged with the V5 epitope.…”
Section: Short Communicationmentioning
confidence: 85%